Advances About Immunoinflammatory Pathogenesis and Treatment in Diabetic Peripheral Neuropathy - Xue, Tianyu; Zhang, Xin; Xing, Yiwen; Liu, Shuhan; Zhang, Lijun; Wang, Xun; Yu, Min (Frontiers in Pharmacology, 2021)
Most diabetic patients develop diabetes peripheral neuropathy (DPN). DPN is related to the increase of inflammatory cells in peripheral nerves, abnormal cytokine expression, oxidative stress, ischemia and pro-inflammatory changes in bone marrow. We reviewed the immunological mechanism of DPN, and summarized the research progress of DPN drug therapy in recent years.